The Effect Of Intrinsic Work Motivation, Extrinsic Work Motivation, Spiritual Vision Leadership, Spiritual Altruistic Love Leadership, And Spiritual Hope/Faith Leadership On Teachers' Performance - Khaerin, Iftah; Sutisna, Deden (Jurnal Ekonomi, 2024)
This study aims to analyze the effect of intrinsic work motivation, extrinsic work motivation, spiritual vision leadership, spiritual altruistic love leadership, and spiritual hope/faith leadership on teacher performance at the Yayasan Indonesia Juara Foundation after the COVID-19 pandemic. The shift from face-to-face to distance learning due to the pandemic has impacted teachers' performance and motivation, highlighting the need for an understanding of the factors that influence their work. Primary and secondary data were collected from 100 teachers at the Foundation using a structured questionnaire and analyzed with SPSS version 25. The results revealed that intrinsic work motivation (t-count = 3.074, p < 0.05) and spiritual altruistic love leadership (t-count = 9.984, p < 0.05) significantly affect teacher performance, while extrinsic work motivation did not show a significant effect (t-count = 0.750, p > 0.05). The simultaneous analysis indicated that the five independent variables together had a significant impact on teacher performance (F-count = 23.520, p < 0.05), explaining 69% of the variation in teacher performance. This study underscores the importance of both intrinsic work motivation and spiritual leadership in enhancing teacher performance, especially in the challenging post-pandemic era. The findings provide valuable insights for educational institutions to strengthen teacher engagement and well-being.